1979
DOI: 10.1073/pnas.76.7.3464
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in clonable B lymphocytes and myeloid progenitors in autoimmune NZB mice.

Abstract: Cloning procedures were used to study B lymphocytes and progenitors of granulocytes and macrophages in NZB mice. Numbers of B cells that were detected in sheep erythrocyte-containing semisolid cultures were only slightly elevated in NZB tissues, and these were normally sensitive to inhibition by anti-,u or anti-b antibodies or prostaglandin E.However, NZB mice rapidly developed large numbers of B cells that could be cloned in the presence of lipopolysaccharide, and these included unusual anti-,u resistant cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 22 publications
3
24
0
Order By: Relevance
“…However, the fact that MRL/lpr mice have circulating immune complexes (23) but no detectable splenic NPY mRNA suggests that there may be an alternative explanation for the enhanced splenic levels of NPY mRNA in the other autoimmune strains used in this study. For instance, Kincade et al (35) reported abnormalities in responsiveness ofhematopoietic stem cells to colony-stimulating factors in the NZB mouse, which may affect megakaryocyte production.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that MRL/lpr mice have circulating immune complexes (23) but no detectable splenic NPY mRNA suggests that there may be an alternative explanation for the enhanced splenic levels of NPY mRNA in the other autoimmune strains used in this study. For instance, Kincade et al (35) reported abnormalities in responsiveness ofhematopoietic stem cells to colony-stimulating factors in the NZB mouse, which may affect megakaryocyte production.…”
Section: Discussionmentioning
confidence: 99%
“…MRL/MP-lpr/lpr (MRL/l) and BXSB mice as well as NZB mice and NZB x NZW F1 hybrids spontaneously develop autoimmune diseases characterized by anti-double-stranded (ds) DNA antibodies, immune-complex glomerulonephritis, and death from renal failure (1). Abnormalities have been found in or attributed to T cells, thymic epithelium, B cells, and/or macrophages in these mice (2)(3)(4)(5)(6)(7)(8). Recently, several groups have shown that the proneness to develop autoimmune diseases actually resides in defects at the lymphoid stem-cell level and that defects of function are not directly attributable to environmental factors such as hormones or viruses (9)(10)(11).…”
mentioning
confidence: 99%
“…Polyclonal activation of B cells might be the critical background abnormality in the pathogenesis of autoimmunity in NZB-derived mice [5][6][7]. The severity of polyclonal B-cell activation might determine the production of autoantibodies and the fate of the autoimmune mice.…”
Section: Introductionmentioning
confidence: 99%